Punishment and forgiveness of sexual crimes: A special reference to sodomy in Calvin’s theology - Magyar, Balázs D. (Verbum et ecclesia, 2022)
In 2017, the huge outpouring of articles and monographs concerning the study of the Reformation made explicitly clear how important social renewal was for the reformers. Doing so, they contributed much to resacralise the spiritual and religious dimensions of family and marital life. Nevertheless, a careful examination of Calvin’s bibliographies shows that there are a great number of articles on Calvin’s social thoughts, but the illumination of his views on sexuality and sexual crimes is still a neglected part of the research. On the basis of Calvin’s Institutes, biblical commentaries and sermons, this article intended to give a case study of his arguments concerning the punishment of sexual immorality. However, Calvin did not expound his detailed evaluation related to sodomy, but the ethical considerations of Apostle Paul (1 Cor 6:9-11) give opportunity to reconstruct his ‘moral codex’. To be sure, in his works Calvin accepted in theory that serious fornication (adultery, homosexuality) should be punished severely; still, he knew well the importance of forgiveness in practice. His pastoral calling was to preach from the hope of mercy; therefore, in the case of fornication - except for abuse, incest or paedophilia - wrongdoers could experience the grace of God. Intradisciplinary and/or interdisciplinary implications: This article is based on the field of systematic theology. The study did not want to inquiry into any direct way into modern or postmodern interpretations of homosexuality but offered an attempt to understand ‘homosexuality’ in its 16th century theological, judicial and historical context.